EFFECT OF COMPENSATION, COMMUNICATION AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT OF TANGSEL POS EMPLOYEES (JAWA POS GROUP) - Arie, Novianto; Budiono Nur Aktif (Dinasti Publisher, 2020)
This study aims to analyze the effect of compensation, communication, and job satisfaction on the organizational commitment of Tangsel Pos employees (Jawa Pos Group). The unit of analysis in this study is employees of Tangsel Pos (Jawa Pos Group), with a population of 53 employees and because the population is less than 100, the sampling method uses a census method where all employees are used as research samples, so the number of samples in the study this is 53 employees. This research uses quantitative analysis method with multiple linear regression using SPSS Version 21. Previously, the questionnaire was tested for validity and reliability and all statements of the questionnaire were valid and reliable. To meet the criteria and requirements for multiple linear regression, this study uses a classic assumption test. The results showed that compensation, communication, and job satisfaction had a positive and significant effect on organizational commitment either partially or simultaneously. The better compensation, communication, and job satisfaction provided to employees, will also be followed by increasing employee commitment to the organization.